Pengaruh Green Marketing, Brand Image, Persepsi Harga Terhadap Minat Beli Produk CLEO Studi Kasus Konsumen CLEO di Tangerang - Moch Altof Egan Nugroho; Ambardi Ambardi (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
Plastic waste is damaging the environment and encouraging people to choose eco-friendly products. Indonesia's waste problem is urgent. Companies are starting to develop products that are safe for the environment. Consumers are turning to chemical-free products to safeguard their health and the environment. CLEO, a drinking water brand from PT Sariguna Primatirta, has been managing this since 2004. CLEO is known for its prices and product quality. This study looks at how green marketing, brand image, and price perceptions affect buying interest in CLEO products among consumers in Tangerang. It uses quantitative methods and a questionnaire. The data analysis is multiple regression analysis. This study shows that green marketing and brand image affect buying interest in CLEO products, but price perception does not. All three variables affect buying interest in CLEO products.